Highlighting of the Interwar identity of the Fokionos Negri street-linear park.: The iconic Lanaras apartment building - Eleftheraki, Georgia; Haniotou, Helene; Markou, Maria (Technical Annals, 2023)
The Greek legal framework for the protection of the architectural heritage of the center of Athens promotes, for historical-political reasons, its archaeological wealth and neoclassical interpretation, neglecting the protection and promotion of important buildings and open spaces of the 20th century which, as modern monuments, complete the city’s image and identity, interpreting its evolution mechanisms and the way that people appropriate it in the everyday life. Our research project aims to study the historic urban landscape of the Fokionos Negri street- linear park that has been formed during the first half of the 20th century and hosts many buildings characteristic of "Athenian modernism", an area of significant importance for the functional and social evolution of the wider center of Athens. The research goals have a triple approach, architecture, landscape and social. One of the main goals is the presentation and analysis of the notable morphological and typological features of the interwar apartment buildings on the street, but also of the history of their people. This approach is presented in the issue we created for one of the Interwar apartment buildings and landmark of the area, the Lanaras family’s apartment building. The project aims to contribute both to the documentation of the interwar architectural heritage of Athens and to the production of a broad framework of knowledge that may be the basis for how to understand and appreciate the historic urban landscape in Greece, in order to elaborate the criteria of its protection and prudent management.